Sosialisasi Pemberian Makanan Bergizi Bubur Kacang Hijau (Vigna Radiata) Pencegahan Stunting di Kelurahan Sonraen Kecamatan Amarasi Selatan - Yosafat Labut; Arfin Mitan, Florentino; Boleng Kelen, Veronika; Indriyati; Likusina Kaha, Hendrikus; Kleden, Marianus (Yayasan Inspirasi El Burhani, 2025)
Introduction: Stunting remains a serious nutritional problem in Indonesia, especially in toddlers, caused by various factors such as inadequate nutritional intake, repeated infections, and lack of psychosocial stimulation. Utilizing local resources such as mung bean porridge can be an alternative solution in stunting prevention efforts due to its high nutritional content. Objective: This activity aims to increase public knowledge about stunting and the benefits of mung bean porridge for the nutrition of vulnerable communities. Method: The outreach and distribution of mung bean porridge was carried out in Sonraen Village, South Amarasi District, East Nusa Tenggara Province, on April 24, 2025, with 25 participants. The implementation process consisted of three stages: requesting permission and coordination with the village government, preparing tools and materials for the outreach, and conducting outreach with health workers from the Community Health Center (Puskesmas) and Posyandu (Integrated Health Post) cadres. Result: As a result, the outreach and distribution of mung bean porridge received a positive response from vulnerable communities. Those present were interested in the mung bean porridge and expressed interest in making it themselves. Conclusion: This activity successfully raised awareness of the importance of balanced nutrition to prevent stunting, as well as providing alternative solutions for using local resources in the stunting eradication program in Sonraen Village, South Amarasi District.